(untitled) (IJOVTECH, 2026)
Introduction of Virtual reality (VR) technologies to information and communication technology (ICT) education has proved to be a good solution to improve the learning and teaching of advanced concepts in networking especially where resources are limited like in Ebonyi State in Nigeria. The research paper examines the usefulness of VR laboratories to enhance student involvement, conceptual knowledge and practical networks knowledge in ICT programs on topics of network topology, protocol simulation, and cybersecurity at tertiary education in Ebonyi State. The mixed-methods research design implied that primary data were obtained involving surveys and experimentation of 250 undergraduate students at Ebonyi State University (EBSU) with the demographic information included, namely, age, gender, and socioeconomic background. The theoretical model is a combination of Technology Acceptance Model (TAM) and constructivist learning theory which is used to analyze user perceptions and learning outcomes. The results show that VR labs are much effective than the traditional technique with 35 percent higher knowledge retention but 42 percent better practical application skills assessed by pre- and post-test scores. Such issues included infrastructure constraints and high implementation expenses but it could be seen in the long-term that there were benefits linked to accessibility and a cost-effective approach. The research uses historical literature concerning the beginning of the 2000s that focuses on hands-on learning based on virtual simulations and the most recent researches published in the past few years that support the idea of immersive VR as an effective tool in STEM education. The solutions suggested are policy support of VR implementation in ICT initiatives in Nigeria and additional education of further trainings of teachers. The current study is related to innovative pedagogies in emerging settings and highlights the potential of VR to eliminate educational disparities related to high-level networking teaching